Local self-interaction correction method with a simple scaling factor. Issue 3 (18th January 2021) - Romero, Selim; Yamamoto, Yoh; Baruah, Tunna; Zope, Rajendra R.
Abstract : The local self-interaction correction method with a simple scaling factor performs better than the Perdew-Zunger self-interaction correction method and also provides a good description of the binding energies of weakly bonded water clusters.  Abstract : A recently proposed local self-interaction correction (LSIC) method [Zope et al., J. Chem. Phys., 2019, 151, 214108] when applied to the simplest local density approximation provides a significant improvement over standard Perdew–Zunger SIC (PZSIC) for both equilibrium properties such as total or atomization energies as well as properties involving stretched bond such as barrier heights. The method uses an iso-orbital indicator to identify the single-electron regions. To demonstrate the LSIC method, Zope et al. used the ratio z σ of von Weizsäcker τ W σ and total kinetic energy densities τ σ, ( z σ = τ W σ / τ σ ) as a scaling factor to scale the self-interaction correction. The present work further explores the LSIC method using a ratio of orbital and spin densities as a simpler scaling factor in place of the ratio of kinetic energy densities. We compute a wide array of both, equilibrium and non-equilibrium properties using LSIC and orbital scaling methods using this simple scaling factor and compare them with previously reported results. Our study shows that LSIC with the simple scaling factor performs better than PZSIC, with results comparable to those obtained by LSIC( z σ ) for most properties, but has slightly larger errors than LSIC( z σ ). Furthermore, we study the binding energies of small water clusters using both scaling factors. Our results show that LSIC with z σ has limitations in predicting the cluster binding energies of weakly bonded systems due to the inability of z σ to distinguish weakly bonded regions from slowly varying density regions. LSIC when used with the density ratio as a scaling factor, on the other hand, provides a good description of water cluster binding energies, thus highlighting the appropriate choice of the iso-orbital indicator.